RESEARCH ON THE INFLUENCE OF THE HAULAGE SPEED OF SHEARER DRUM LOAD UNDER THE RECONSTRUCTION THEORY - CHEN HongYue; WANG Xin; MAO Jun; ZHANG Yu (Jixie qiangdu)
In order to study the haulage speed of shearer drum load effect by Tikhonov regularization method,pick load reconstruction model was constructed,and the haulage speed and pick load was deduced. The roller and haulage unit of mutual coupling system dynamics model was established,the model solved by using numerical simulation method,and the results using statistical methods that different haulage speed shearer drum three-axis force the average value and the standard difference,validated by experiment. The results show that simulation results and experimental results in the mean and the standard deviation error range is less than 5%,to verify the correctness of the theoretical model.